"The One Who Knows the Value of Words": The Aşiq of Azerbaijan. (6th December 2015) - Baghirova, Sanubar
Abstract : "The one who knows the value of words": this is a line from the most famous aşιq poem in the Azerbaijani language in which the author, Aşιq Əlǝsgǝr, describes the qualities of the ideal aşιq . Interpreted in much of the western world as a traditional bardic art, Azerbaijanis regard the art of the aşιq (pl. aşιqlar ) as a high-class professional syncretic form with its own established canons, traditional forms of teaching and learning, and numerous regional traditions of performance. This article is about the aşιqlar who live and practise their arts in the Azerbaijan Republic.